斜齿圆柱齿轮啮合刚度波动的变化规律研究 - 丁云飞; 刘岚; 吴立言; 常乐浩 (Jixie chuandong)
By using the finite element method,the mesh stiffness and its fluctuation value of helical gears with different parameters are calculated respectively,and the change law of mesh stiffness fluctuation is summarized.The results show that contact ratios are the main factors that affect the fluctuation value of mesh stiffness when the gear parameters change.The fluctuation value of mesh stiffness has a minimum when the transverse contact ratios or face contact ratio is an integer.And in the meantime,the total length of contact line doesn’t change during one whole meshing period.The conclusions can be used to guide the selection and optimization of gear transmission parameter.